Synthetic method of LSC-GDC complex phase powder material, air electrode and solid oxide battery
Synthesis of LSC-GDC composite powder material through flame method solves the problems of cumbersome processes and insufficient contact, achieves uniform distribution and high reactivity of nanoparticles, and improves the performance and stability of solid oxide batteries.
Patent Information
- Application Number
- CN202411311628.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The existing LSC-GDC composite material synthesis method has cumbersome processes and takes a long time. The contact between the two phases is insufficient, resulting in Sr diffusion and oxygen vacancy problems. It is difficult to control the particle size distribution during the preparation process of the flame method, and the product morphology is uneven.
The LSC-GDC compound phase powder material was synthesized by flame method, and the precursor solution was prepared and atomized with the carrier gas and sprayed into the flame to form nucleation and growth. The nanoparticles were formed by combining deionized water and alcohol solvents to control the carrier flow. Gas flow rate and flame conditions achieve the formation of single-use synthetic nanoparticles.
The synthesis process is simplified, the uniform distribution of nanoparticles and high specific surface area are achieved, the reactive activity of the material is improved, and the air electrode material is suitable for solid oxide batteries, improving the performance and stability of the battery.
Smart Images

Figure CN119191371A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano material preparation, and in particular to a LSC-GDC composite powder material synthesis method, an air electrode and a solid oxide battery. Background Art
[0002] Solid oxide batteries, as one of the ways to efficiently utilize hydrogen, can convert chemical energy into electrical energy. The reverse process can also convert water and / or carbon dioxide into chemical energy in the form of H2 and / or CO for storage by providing electrical energy, which has attracted widespread attention. The traditional air electrode material of solid oxide batteries is La 1-x Sr x CoO 3-δ (LSC), but the element Sr in it is easy to diffuse in a high temperature environment. Studies have shown that adding Ce to the LSC material system 0.8 G 0.2 O 1.95 (GDC) forms a composite material, which can transfer oxygen vacancies from the LSC surface to GDC, alleviating the phenomenon that excessive surface oxygen vacancies attract Sr in the bulk phase to migrate to the surface.
[0003] The composite materials of perovskite oxides are currently mainly synthesized through mechanical mixing or common material preparation methods (such as sol-gel, hydrothermal method, spray drying, solid phase method, etc.) through multiple steps. However, mechanical mixing leads to insufficient contact between LSC and GDC, and GDC cannot absorb oxygen vacancies on the surface of LSC and inhibit the diffusion of Sr. In addition, for example, the sol-gel method for synthesizing metal oxides is generally to synthesize LSC and GDC separately, and then synthesize LSC-GDC by the sol-gel method, wherein the synthesis of LSC and GDC undergoes sol-gel, drying, calcination and other processes, which takes about 4-5 days, and then the sol-gel method is used to synthesize LSC-GDC, which takes another 4-5 days. It has many problems such as cumbersome steps, long multi-step calcination time, and uneven element distribution; the spray drying method also requires multi-step calcination, ball milling and drying, and the particle size of the synthesized LSC-GDC composite powder material is generally above 100nm; the hydrothermal method synthesizes less, and the high-pressure operation is prone to irreversible danger due to improper operation; the solid-phase method synthesizes LSC-GDC composite materials, although the output is large, but its particle size is large, and the corresponding reaction active sites are small. In short, when synthesizing LSC-GDC composite materials, the route of separate synthesis and then two-phase synthesis is generally adopted, which is cumbersome and time-consuming, and the low contact probability between the two phases is not conducive to catalysis.
[0004] As a rapid synthesis technology, the flame method has a fast reaction. Compared with other preparation methods of LSC-GDC composite materials, it can greatly shorten the preparation cycle and improve production efficiency. However, when the existing technology uses the flame method to prepare LSC-GDC composite materials, LSC or GDC is first synthesized separately, and then the composite material is prepared. It cannot fully demonstrate the advantages of the flame method. In addition, due to the characteristics of high temperature and rapid reaction, it is difficult to control the particle size distribution of the product, and the product morphology may not be uniform enough. Summary of the invention
[0005] In order to solve the above technical problems, the embodiment of the present invention discloses a method for synthesizing a LSC-GDC composite powder material, comprising the following steps:
[0006] Preparation of precursor solution: According to La 0.6 Sr 0.4 CoO 3-δ -Ce 0.8 G 0.2 O 1.95 The chemical composition of the present invention is to weigh metal salt solutes of corresponding stoichiometric ratios, wherein the metal salt solutes are compounds containing La and acid radicals, compounds containing Sr and acid radicals, compounds containing Co and acid radicals, compounds containing Ce and acid radicals, and compounds containing Gd and acid radicals, wherein the acid radical is one of nitrate, acetate, propionate, and carbonate, and the metal salt solutes are dissolved in a solvent to form a precursor solution, wherein the components of the solvent are deionized water, alcohols, acids, ethers, and esters, or a combination of two or more thereof. When the components of the solvent are two or more and deionized water is contained, the volume fraction of deionized water in the solvent is x, 0. <x≤14%,
[0007] Among them, δ is the coefficient of oxygen vacancies, which represents the difference between the actual number of oxygen ions present in the chemical formula and the theoretical number;
[0008] Flame method for synthesizing composite materials: atomize the precursor solution and the carrying gas together, spray them into the flame for nucleation and growth, and collect the LSC-GDC composite powder material, wherein the carrying gas is air or oxygen, and the flow rate of the carrying gas is 3-15L / min;
[0009] Wherein, the nanoparticle size of the LSC-GDC composite powder material is 1-10nm.
[0010] By adopting the above technical scheme, the characteristics of the flame method can be fully utilized. The synthesis does not need to be divided into two steps, but the required LSC-GDC composite powder material can be synthesized at one time. Not only does it not require multi-step calcination, the preparation process is very simple, and the two phases are in full contact. Through the regulation of the process, nanoparticles with small particle size and uniform distribution can be obtained. The material has a large specific surface area and many reactive active sites. It is particularly suitable for use as an air electrode material for solid oxide batteries. The battery prepared using the LSC-GDC composite powder material has better performance. The method is simple to operate, stable to control, and highly repeatable, and is suitable for large-scale preparation of the required powder.
[0011] Optionally, the solvent comprises deionized water and ethanol, and the volume fraction x of the deionized water in the solvent satisfies 8≤x≤14%.
[0012] Optionally, the molar concentration of the metal element in the precursor solution is 0.01-1 mol / L, and the metal element is La, Sr, Co, Ce and Gd.
[0013] Optionally, the pumping rate of the precursor solution is 0.1-10 mL / min.
[0014] Optionally, the tolerance factor t of the nanoparticles of the LSC-GDC composite powder material satisfies t∈[0.7,1.1], and t is calculated according to formula (1):
[0015]
[0016] Among them, r A is the ionic radius of La ion, r B is the ionic radius of the Sr ion, r O is the ionic radius of O ion.
[0017] Optionally, the flame is generated by igniting a mixture of combustible gas and oxidant, the combustible gas is a gaseous hydrocarbon fuel, the oxidant is air or oxygen, the flow rate of the combustible gas is 0.5-6L / min, and the flow rate of the oxidant is 2.5-30L / min.
[0018] Optionally, the flame type of the flame is a plane flame, and the equivalence ratio of the plane flame is 0.9-1.1.
[0019] Optionally, the plane flame is generated by igniting a mixture of methane and air, the flow rate of methane is 1.5 L / min, and the flow rate of air is 15 L / min.
[0020] According to another specific embodiment of the present invention, an embodiment of the present invention discloses an air electrode, wherein the air electrode comprises a first multiphase powder material, wherein the first multiphase powder material is a LSC-GDC multiphase powder material synthesized by the above-mentioned synthesis method.
[0021] By adopting the above technical solution, the performance of the air electrode is stable and the durability is better.
[0022] Optionally, the air electrode is composed of a first complex phase powder material and a second complex phase powder material, the second complex phase powder material is a LSC-GDC complex phase powder material prepared by spray drying, and the mass of the first complex phase powder material accounts for 10-50% of the total mass of the first complex phase powder material and the second complex phase powder material.
[0023] According to another specific embodiment of the present invention, an embodiment of the present invention discloses a solid oxide battery, and the solid oxide battery includes the above-mentioned air electrode.
[0024] By adopting the above technical solution, the battery performance is improved and the use is more stable and reliable. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram of a flame synthesis device according to an embodiment of the present invention is shown;
[0026] FIG2( a ) shows a TEM image of the LSC-GDC composite powder material of Example 1 of the present invention;
[0027] FIG2( b ) shows a TEM image of the distribution of elements of the LSC-GDC composite powder material of Example 1 of the present invention;
[0028] Figure 3 The XRD diagram of the LSC-GDC composite powder material of Example 1 of the present invention is shown;
[0029] Figure 4 The XRD diagram of the LSC-GDC composite powder material of Comparative Example 2 of the present invention is shown;
[0030] Figure 5 The XRD diagram of the LSC-GDC composite powder material of Comparative Example 4 of the present invention is shown;
[0031] FIG6( a) shows a TEM image of the LSC-GDC composite powder material of Comparative Example 4 of the present invention;
[0032] FIG6( b ) shows a TEM image of the distribution of elements of the LSC-GDC composite powder material of Comparative Example 4 of the present invention;
[0033] Figure 7 The TEM image of the LSC-GDC composite powder material of Comparative Example 3 of the present invention is shown;
[0034] FIG8( a ) shows the volt-ampere characteristic test results of application examples 1-5 and comparative example 1 of the present invention at 850° C.;
[0035] FIG8( b ) shows the stability test results of Application Example 3 and Application Comparative Example 1 of the present invention at a potential of 0.85 V. FIG. DETAILED DESCRIPTION
[0036] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this embodiment. On the contrary, the purpose of introducing the invention in conjunction with the embodiment is to cover other options or modifications that may be extended based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0037] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0038] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0039] The first aspect of the present invention discloses a method for synthesizing a LSC-GDC composite powder material, comprising the following steps:
[0040] Preparation of precursor solution: According to La 0.6 Sr 0.4 CoO 3-δ -Ce 0.8 G 0.2 O 1.95The chemical composition of the present invention is to weigh metal salt solutes of corresponding stoichiometric ratios, wherein the metal salt solutes are compounds containing La and acid radicals, compounds containing Sr and acid radicals, compounds containing Co and acid radicals, compounds containing Ce and acid radicals, and compounds containing Gd and acid radicals, wherein the acid radical is one of nitrate, acetate, propionate, and carbonate, and the metal salt solutes are dissolved in a solvent to form a precursor solution, wherein the components of the solvent are deionized water, alcohols, acids, ethers, and esters, or a combination of two or more thereof. When the components of the solvent are two or more and deionized water is contained, the volume fraction of deionized water in the solvent is x, 0. <x≤14%,
[0041] Among them, δ is the coefficient of oxygen vacancies, which represents the difference between the actual number of oxygen ions present in the chemical formula and the theoretical number;
[0042] Flame method for synthesizing composite materials: atomize the precursor solution and the carrying gas together, spray them into the flame for nucleation and growth, and collect the LSC-GDC composite powder material, wherein the carrying gas is air or oxygen, and the flow rate of the carrying gas is 3-15L / min;
[0043] Wherein, the nanoparticle size of the LSC-GDC composite powder material is 1-10nm.
[0044] In this method, two metal salt solutions of metal oxides are prepared, stirred and mixed thoroughly, and flame synthesis is performed to obtain La 0.6 Sr 0.4 CoO 3-δ -Ce 0.8 G 0.2 O 1.95 The LSC-GDC composite powder material is prepared. Specifically, a compound containing La and an acid radical, a compound containing Sr and an acid radical, a compound containing Co and an acid radical, a compound containing Gd and an acid radical, and a compound containing Ce and an acid radical are used in a molar ratio of 0.6:0.4:1:0.2:0.8. The inventors found that although the flame method is to mix the raw materials, it can synthesize La in a directional manner after simple mixing. 0.6 Sr 0.4 CoO 3-δ and Ce 0.8 G 0.2 O 1.95 , and La 0.6 Sr 0.4 CoO 3-δ and Ce 0.8 G 0.2 O 1.95The two form a close composite relationship, the interface layer is optimized, and the transfer effect of oxygen vacancies is improved, which is helpful to improve the electrical performance of the prepared solid oxide battery. This method does not need to prepare one of them first and then synthesize the composite material, which greatly simplifies the operation steps and has a relatively simple process. Specifically, in this synthesis method, the two phases can be fully contacted, and the solution is broken and atomized into small droplets by using the carrying gas, and then sprayed into a stable flame field to form a spray jet flame. The fine droplets of the atomized precursor solution undergo solvent evaporation and acid radical salt decomposition processes almost simultaneously at high temperature to form precursor vapor, which then undergoes nucleation and growth to form nano-scale particles. The carrying gas is air or oxygen, and the flow rate of the carrying gas is 3-15L / min. When the flow rate of the carrying gas is higher than this range, the residence time of the precursor in the flame is too short, and the product will not form a stable phase; when it is lower than this flow range, the product size will become larger. Controlling the flow rate to 3-15L / min helps to form composite material nanoparticles with a particle size of 1-10nm.
[0045] This method uses a flame method combined with process control to prepare composite material nanoparticles with a particle size of 1-10nm. The elements are evenly distributed, so that the nanoparticles have a very high specific surface area and have more reactive sites that can be used for electrochemical reactions, which helps to improve the efficiency of electrocatalysts in solid oxide batteries. In addition, the compositeness of the two phases is improved by reasonable regulation of the flame method process, and the formation of nanoparticles with a particle size range of 1-10nm and uniform distribution is helped by parameter control, solvent selection, etc., which can form a more compact electrode structure and help improve the conductivity of electrons and ions. At the same time, more channels can also be provided, thereby enhancing the diffusion of oxygen to the electrode surface and improving the power density of the battery. Furthermore, this type of composite material nanoparticles can enhance the mechanical stability and chemical stability of the battery and reduce structural degradation during long-term operation.
[0046] Specifically, the compound containing La and an acid radical is lanthanum nitrate, lanthanum acetate, lanthanum propionate, or lanthanum carbonate, the compound containing Sr and an acid radical is strontium nitrate, strontium acetate, strontium propionate, or strontium carbonate, the compound containing Co and an acid radical is cobalt nitrate, cobalt acetate, cobalt propionate, or cobalt carbonate, the compound containing Ce and an acid radical is cerium nitrate, cerium acetate, cerium propionate, or cerium carbonate, the compound containing Gd and an acid radical is gadolinium nitrate, gadolinium acetate, gadolinium propionate, or gadolinium carbonate. More specifically, the metal salt solutes used are lanthanum nitrate, strontium nitrate, cobalt nitrate, cerium nitrate, and gadolinium nitrate.
[0047] In a specific embodiment of the present invention, the solvent is composed of one or a combination of two or more of deionized water, alcohols, acids, ethers, and esters. When the solvent is composed of two or more components and contains deionized water, the volume fraction of deionized water in the solvent is x, where 0 < x ≤ 14%. Specifically, for example, the solvent is deionized water and ethanol, with the volume of deionized water accounting for 10% and the volume of propanol accounting for 90%. If the volume fraction of deionized water exceeds 14%, the generated composite material nanoparticles may agglomerate, and it is difficult for metal oxides to form a phase. Additionally, it is not conducive to the combustion of the precursor solution, and the preparation process is difficult to carry out.
[0048] Preferably, the solvent is composed of deionized water and ethanol, and the volume fraction x of deionized water in the solvent satisfies 8 ≤ x ≤ 14%. When the solvent is composed of deionized water and ethanol within a certain volume range, it can appropriately help generate the required flame and contribute to the formation of nanoparticles with a certain particle size range and uniform distribution.
[0049] In a specific embodiment of the present invention, the molar concentration of metal elements in the precursor solution is 0.01 - 1 mol / L, and the metal elements are La, Sr, Co, Ce, and Gd, which helps to make nucleation and growth as expected and control the particle size and particle size distribution.
[0050] In a specific embodiment of the present invention, the pumping rate of the precursor solution is 0.1 - 10 mL / min. The pumping rate affects the residence time of the precursor solution in the flame and the growth process of the particles. An appropriate pumping rate can facilitate the full decomposition of the solution in the flame and the formation of uniform nanoparticles.
[0051] In a specific embodiment of the present invention, the tolerance factor t of the nanoparticles of the LSC - GDC composite powder material satisfies t ∈ [0.7, 1.1], and t is calculated according to formula (1):
[0052]
[0053] where r A is the ionic radius of La ions, r B is the ionic radius of Sr ions, r O is the ionic radius of O ions. When t satisfies t ∈ [0.7, 1.1], it can ensure that the generated composite powder material is of the LSC - GDC type and a stable perovskite structure is formed.
[0054] In a specific embodiment of the present invention, the flame is generated by igniting the mixture of combustible gas and oxidant. The combustible gas is a gaseous hydrocarbon fuel, the oxidant is air or oxygen, the flow rate of the combustible gas is 0.5 - 6 L / min, and the flow rate of the oxidant is 2.5 - 30 L / min.
[0055] By controlling the precursor solution pumping rate, the carrying gas flow rate, the combustible gas flow rate, and the oxidant flow rate, the introduction of the precursor solution, the carrying gas, the combustible gas, and the oxidant can be coordinated with each other to achieve an ideal reaction condition, so as to achieve effective decomposition of the precursor and uniform growth of nanoparticles in the flame, control the particle size of the nanoparticles, and ensure the quality and performance of the powder.
[0056] In a specific embodiment of the present invention, the flame type is a planar flame, and the equivalence ratio of the planar flame is 0.9-1.1. The planar flame is a special type of flame that provides a uniform combustion environment. The equivalence ratio of the planar flame is controlled between 0.9-1.1, ensuring the sufficiency and stability of the combustion, so that the precursor solution can be uniformly decomposed and synthesized in the flame, which can further optimize the synthesis process of the nanoparticles, including the size, shape, dispersity and phase composition of the particles.
[0057] In a specific embodiment of the present invention, a planar flame is generated by igniting a mixture of methane and air, wherein the flow rate of methane is 1.5 L / min, and the flow rate of air is 15 L / min, which is approximately chemical equivalent ratio combustion, the flame temperature is the highest, and the flame is the most stable, providing a stable high-temperature temperature field for the combustion of the precursor liquid.
[0058] In a specific embodiment of the present invention, the flame synthesis is mainly carried out as follows Figure 1 The process is carried out by using the device shown in the figure, which includes a gas supply system, a gas flow control system, a circulating cooling system, an atomization system, a burner, a collecting device, etc.
[0059] Specifically, the gas supply system is composed of a flow-carrying gas pipeline 2, a combustible gas and an oxidant pipeline 4, and the gas flow rate is precisely controlled by a gas flow control system (not shown in the figure), for example, by adjusting the flow rate of the combustible gas and the oxidant mixed gas to form a stable high-temperature premixed plane flame. Specifically, the oxidant control switch is turned on first, and then the combustible gas control switch is turned on for premixing, and then the premixed gas is ignited with an igniter to prevent flashback, and a flame field can be formed at the burner 5.
[0060] The device also includes an atomization system. After the flame is stabilized, the flow-carrying gas switch is turned on, and the flow-carrying gas enters through the flow-carrying gas channel 2, and the precursor solution enters the precursor pipeline 3 through the injection pump 1. Then the flow-carrying gas and the precursor solution arrive at the two-fluid nozzle 6 in the center of the burner 5 together, and are atomized by the two-fluid nozzle 6. The atomized flow-carrying gas and the precursor solution burn under the action of the flame field to form a stable jet flame. In the jet flame, the tiny droplets almost simultaneously evaporate the solvent and decompose the acid salt at high temperature, forming precursor vapor, which then undergoes nucleation and growth to form nano-scale particles. The particles are collected by the glass fiber membrane 7 to obtain a powder material. The collection device is connected to a water cooling system to prevent the glass fiber paper from burning due to high temperature.
[0061] The second aspect of the present invention discloses an air electrode, which includes a first multiphase powder material, and the first multiphase powder material is a LSC-GDC multiphase powder material obtained by the above method.
[0062] In a specific embodiment of the present invention, the air electrode is composed of a first composite powder material and a second composite powder material, the second composite powder material is a LSC-GDC composite powder material prepared by a spray drying method, and the mass of the first composite powder material accounts for 10-50% of the total mass of the first composite powder material and the second composite powder material. The blending of the first composite powder material can improve the battery performance, and when the mass of the first composite powder material accounts for 10-50% of the total mass of the first composite powder material and the second composite powder material, the battery volt-ampere characteristics and long-term stability are improved.
[0063] The third aspect of the present invention discloses a solid oxide battery, which includes the above-mentioned air electrode.
[0064] The air electrode and solid oxide battery of the present invention have stable performance, can operate for a long time, and have improved electrochemical performance.
[0065] This will be explained below through a more specific implementation method.
[0066] (I) Embodiment 1-6, Application Embodiment 1-5:
[0067] Examples 1-6 are LSC-GDC composite powder materials prepared by flame method, and application examples 1-5 are solid oxide batteries comprising the LSC-GDC composite powder materials of Example 1. The specific preparation process is as follows:
[0068] (1) Preparation of Example 1
[0069] Prepare a precursor solution: weigh La(CH3COOH)3, Sr(CH3COOH)2, Co(CH3COOH)2, Gd(CH3COOH)3, and Ce(CH3COOH)3 in a molar ratio of 0.6:0.4:1:0.2:0.8, and dissolve them in a mixed solvent of propanol and propionic acid to form a precursor solution, wherein the volume ratio of propionic acid to propanol in the mixed solvent is 1:1, and the molar concentration of the metal element in the precursor solution is 0.1 mol / L;
[0070] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 8 L / min. The precursor solution is then pumped in at a rate of 4 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0071] (2) Preparation of Example 2
[0072] Prepare a precursor solution: weigh La(NO3)3·6H2O, Sr(NO3)2·6H2O, Co(NO3)2·6H2O, Gd(NO3)3·6H2O and Ce(NO3)3·6H2O in a molar ratio of 0.6:0.4:1:0.2:0.8, dissolve them in a mixed solvent of ethanol and deionized water, and mix and stir them thoroughly to form a precursor solution, wherein the volume fraction of deionized water in the mixed solvent is 10%, and the molar concentration of the metal element in the precursor solution is 0.1 mol / L;
[0073] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 8 L / min. The precursor solution is then pumped in at a rate of 4 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0074] (3) Preparation of Example 3
[0075] Prepare a precursor solution: weigh La(CH3COOH)3, Sr(CH3COOH)2, Co(CH3COOH)2, Gd(CH3COOH)3, and Ce(CH3COOH)3 in a molar ratio of 0.6:0.4:1:0.2:0.8, and dissolve them in a mixed solvent of propanol and propionic acid to form a precursor solution, wherein the volume ratio of propionic acid to propanol in the mixed solvent is 1:1, and the molar concentration of the metal elements in the precursor solution is 0.1 mol / L;
[0076] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 8 L / min. The precursor solution is then pumped in at a rate of 3 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0077] (4) Preparation of Example 4
[0078] Prepare a precursor solution: weigh La(CH3COOH)3, Sr(CH3COOH)2, Co(CH3COOH)2, Gd(CH3COOH)3, and Ce(CH3COOH)3 in a molar ratio of 0.6:0.4:1:0.2:0.8, and dissolve them in a mixed solvent of propanol and propionic acid to form a precursor solution, wherein the volume ratio of propionic acid to propanol in the mixed solvent is 1:1, and the molar concentration of the metal elements in the precursor solution is 0.1 mol / L;
[0079] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 10 L / min. The precursor solution is then pumped in at a rate of 3 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0080] (5) Preparation of Example 5
[0081] Prepare a precursor solution: weigh La(CH3COOH)3, Sr(CH3COOH)2, Co(CH3COOH)2, Gd(CH3COOH)3, and Ce(CH3COOH)3 in a molar ratio of 0.6:0.4:1:0.2:0.8, and dissolve them in a mixed solvent of propanol and propionic acid to form a precursor solution, wherein the volume ratio of propionic acid to propanol in the mixed solvent is 1:1, and the molar concentration of the metal elements in the precursor solution is 0.1 mol / L;
[0082] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 8 L / min. The precursor solution is then pumped in at a rate of 6 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0083] (6) Preparation of Example 6
[0084] Prepare a precursor solution: weigh La(CH3COOH)3, Sr(CH3COOH)2, Co(CH3COOH)2, Gd(CH3COOH)3, and Ce(CH3COOH)3 in a molar ratio of 0.6:0.4:1:0.2:0.8, and dissolve them in propionic acid solvent to form a precursor solution, wherein the molar concentration of the metal elements in the precursor solution is 0.1 mol / L;
[0085] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 8 L / min. The precursor solution is then pumped in at a rate of 4 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0086] (7) Preparation of Application Example 1
[0087] Application Example 1: Application Example 1 is a solid oxide battery, which has an air electrode, and the powder material of the air electrode is a first composite powder material and a second composite powder material. The first composite powder material is the LSC-GDC composite powder material prepared by the flame synthesis method in Example 1, and the second composite powder material is the LSC-GDC composite powder material prepared by the spray drying method, wherein the mass of the first composite powder material accounts for 10% of the total mass of the first and second composite powder materials, and is recorded as LSC-GDC F10 The specific preparation process of the second composite powder material is as follows: La(NO3)3·6H2O, Sr(NO3)2·6H2O, Co(NO3)2·6H2O, Gd(NO3)3·6H2O and Ce(NO3)3·6H2O are dissolved in water at a molar ratio of 0.6:0.4:1:0.2:0.8, and spray dried. The spray drying temperature is set to 240°C, and the powder is collected. The collected powder is then placed in a muffle furnace and heated to 800°C at a rate of 3°C / min. After calcination for 3 hours, the second composite powder material is obtained.
[0088] (8) Preparation of Application Example 2
[0089] Application Example 2 is a solid oxide battery, which is different from Application Example 1 only in that the mass ratio of the first composite powder material in the powder material is 20%, which is recorded as LSC-GDC. F20 .
[0090] (9) Preparation of Application Example 3
[0091] Application Example 3 is a solid oxide battery, which is different from Application Example 1 only in that the mass ratio of the first composite powder material in the powder material is 30%, denoted as LSC-GDC F30 .
[0092] (10) Preparation of Application Example 4
[0093] Application Example 4 is a solid oxide battery, which is different from Application Example 1 only in that the mass ratio of the first composite powder material in the powder material is 40%, denoted as LSC-GDC F40 .
[0094] (11) Preparation of Application Example 5
[0095] Application Example 5 is a solid oxide battery, which is different from Application Example 1 only in that the mass ratio of the first composite powder material in the powder material is 50%, which is recorded as LSC-GDC. F50 .
[0096] (II) Comparative Examples 1-4, Application Comparative Example 1:
[0097] Comparative Examples 1 and 2 prepare LSC-GDC composite powder materials by flame synthesis, Comparative Example 3 prepares LSC-GDC composite powder materials by solution gel method, and Comparative Example 4 prepares LSC-GDC composite powder materials by spray drying method. Application Comparative Example 1 is a solid oxide battery containing only the LSC-GDC composite powder materials of Comparative Example 4 in the air electrode, and the specific preparation method is as follows:
[0098] (1) Preparation of Comparative Example 1
[0099] Prepare a precursor solution: weigh La(NO3)3·6H2O, Sr(NO3)2·6H2O, Co(NO3)2·6H2O, Gd(NO3)3·6H2O and Ce(NO3)3·6H2O in a molar ratio of 0.6:0.4:1:0.2:0.8, dissolve them in propanol and deionized water, and mix and stir them thoroughly to form a precursor solution, wherein the volume fraction of deionized water is 20%, the volume fraction of propanol is 80%, and the molar concentration of the metal element is 0.1 mol / L;
[0100] Flame method for synthesizing composite materials: first introduce air (oxidant) and control the flow rate to 15L / min, then introduce methane (combustible gas) and control the flow rate to 1.5L / min, use an igniter to ignite, and form a stable planar flame at the nozzle of the flat flame burner. The equivalence ratio of the planar flame is 1. After the planar flame is stable, introduce oxygen (carrying gas) and control the flow rate to 8L / min. Then pump the precursor solution at a rate of 4mL / min. It was found that a jet flame could not be formed and nucleation could not be performed.
[0101] (2) Preparation of Comparative Example 2:
[0102] Prepare a precursor solution: dissolve La(NO3)3·6H2O, Sr(NO3)2·6H2O, Co(NO3)2·6H2O, Gd(NO3)3·6H2O and Ce(NO3)3·6H2O in ethanol and deionized water in a molar ratio of 0.6:0.4:1:0.2:0.8, and mix and stir to form a precursor solution, wherein the volume fraction of deionized water is 15%, and the molar concentration of the metal element is 0.1 mol / L;
[0103] Flame method for synthesizing composite materials: first, air (oxidant) is introduced with a flow rate controlled at 15 L / min, and then methane (combustible gas) is introduced with a flow rate controlled at 1.5 L / min. The mixture is ignited using an igniter to form a stable plane flame at the nozzle of the flat flame burner. The equivalence ratio of the plane flame is 1. After the plane flame is stable, oxygen (carrying gas) is introduced with a flow rate controlled at 8 L / min. The precursor solution is then pumped in at a rate of 4 mL / min. The precursor solution is atomized into small droplets and then burns with oxygen to form a stable jet flame, which nucleates, generates, and collects the LSC-GDC composite powder material.
[0104] (3) Preparation of Comparative Example 3
[0105] Comparative Example 3 is a LSC-GDC composite powder material prepared by a solution gel method, and the specific preparation process is as follows:
[0106] Weigh La(CH3COOH)3, Sr(CH3COOH)2, Co(CH3COOH)2 in a molar ratio of 0.6:0.4:1, and 3+ , Sr 2+ 、Co 2+ ): citric acid: ethylene glycol in a ratio of 1:4:8 are weighed and mixed to obtain a first solution;
[0107] Weigh Gd(CH3COOH)3 and Ce(CH3COOH)3 in a molar ratio of 0.2:0.8, and add the metal cations (Gd 3 + 、Ce 3+ ): citric acid: ethylene glycol in a ratio of 1:4:8 are weighed and mixed to obtain a second solution;
[0108] The first solution and the second solution were stirred to form a colloidal material, and then placed in a muffle furnace and calcined at 300 degrees Celsius for 10 hours. After being taken out, they were calcined at 900 degrees Celsius for two hours to obtain powdered LSC and powdered GDC materials. The two powders were then mixed to obtain a LSC-GDC composite powder material.
[0109] (4) Preparation of Comparative Example 4
[0110] Comparative Example 4 is a LSC-GDC composite powder material prepared by spray drying, and the specific preparation process is as follows:
[0111] The precursors La(NO3)3·6H2O, Sr(NO3)2·6H2O, Co(NO3)2·6H2O, Gd(NO3)3·6H2O and Ce(NO3)3·6H2O were dissolved in water at a molar ratio of 0.6:0.4:1:0.2:0.8, and spray dried. The spray drying temperature was set to 240°C. The powders were collected and then placed in a muffle furnace and raised to 800°C at a rate of 3°C / min. After calcination for 3 hours, the second composite powder material was obtained.
[0112] (5) Application Comparative Example 1
[0113] Application Comparative Example 1 is a solid oxide battery, and its air electrode powder material is all LSC-GDC composite powder material prepared by spray drying in Comparative Example 4, denoted as LSC-GDC F0 .
[0114] (III) Performance Characterization
[0115] (1) Microscopic characterization
[0116] The nanoparticles of Examples 1-6 were processed to prepare transmission electron microscope (TEM) samples, and the samples were analyzed and the particle size was calculated. It was found that the particle size of the nanoparticles of Examples 1-6 was 1-10 nm. The TEM images of Example 1 are shown in Figures 2(a) and 2(b). As can be seen from Figure 2(a), the particle size of the nanoparticles is in the range of 3-10 nm, and the particle size distribution is relatively uniform. In particular, it can be seen from Figure 2(b) that the elements of the composite material are evenly distributed.
[0117] X-ray diffraction (XRD) analysis was also performed on Example 1. Figure 3 As shown, with La 0.6 Sr 0.4 CoO 3-δ (PDF#97-018-4072) and Ce 0.8 G 0.2 O 1.95 (PDF#97-018-2976) The characteristic peaks of the standard card correspond to each other, indicating that the product has good crystallinity and high purity.
[0118] X-ray diffraction (XRD) analysis was performed on Comparative Example 2. Figure 4 As shown, no stable crystalline phase is formed.
[0119] The nanoparticles of Comparative Example 3 were processed to prepare transmission electron microscopy (TEM) samples for analysis. Figure 7 As shown, the morphology of the nanoparticles is irregular, the elements are unevenly dispersed, and agglomeration occurs.
[0120] X-ray diffraction (XRD) analysis was performed on Comparative Example 4. Figure 5 As shown, no stable crystalline phase is formed. At the same time, the sample is processed to prepare a transmission electron microscope (TEM) sample for analysis. As shown in FIG6(a), the particle size of the nanoparticles is measured and calculated. It is found that the particle size of the nanoparticles in Example 4 ranges from 50 to 320 nm, and the particle size distribution range is wide. In particular, it can be seen from FIG6(b) that the elements of the composite material are agglomerated and unevenly distributed.
[0121] (2) Battery electrical performance characterization
[0122] The volt-ampere characteristics of application examples 1-5 and application comparative example 1 were tested, and the test method was as follows:
[0123] Using an electrochemical workstation, after the open circuit voltage stabilized, a linear voltammetric scan was performed on the battery from the open circuit voltage to 0 V.
[0124] The stability test was performed on Application Example 3 and Application Comparative Example 1, and the test method was as follows:
[0125] The voltage was set to 0.85 V, 50 mL / min of hydrogen was introduced into the fuel electrode side of the battery, and 250 times the gas flow rate of the fuel electrode gas was introduced into the air electrode. The test was performed for 100 hours, and the battery attenuation was observed.
[0126] As shown in Figure 8(a), with the increase of flame-synthesized powder, the performance of the fuel cell shows a trend of first increasing and then decreasing, but the performance of the battery doped with flame-synthesized powder is better than that without doping. The performance of the powder reaches the best when it is mixed with 30%, mainly because the three-phase interface of the solid oxide fuel cell is best optimized at this time, and the performance of the battery is improved. As shown in Figure 8(b), in the durability test, it can be found that the battery with added flame-synthesized powder has better performance and durability than the pure spray-dried synthesized powder.
[0127] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. A method for synthesizing a LSC-GDC composite powder material, characterized in that: The steps include: Preparation of precursor solution: According to La 0.6 Sr 0.4 CoO 3-δ -Ce 0.8 G 0.2 O 1.95 The chemical composition of the present invention is to weigh a metal salt solute of a corresponding stoichiometric ratio, wherein the metal salt solute is a compound containing La and an acid radical, a compound containing Sr and an acid radical, a compound containing Co and an acid radical, a compound containing Ce and an acid radical, and a compound containing Gd and an acid radical, wherein the acid radical is one of nitrate, acetate, propionate, and carbonate, and the metal salt solute is dissolved in a solvent to form a precursor solution, wherein the solvent is composed of one or a combination of two or more of deionized water, alcohols, acids, ethers, and esters. When the solvent is composed of two or more components and contains deionized water, the volume fraction of the deionized water in the solvent is x, 0 <x≤14%, Among them, δ is the coefficient of oxygen vacancies, which represents the difference between the actual number of oxygen ions present in the chemical formula and the theoretical number; Flame method for synthesizing composite materials: atomizing the precursor solution and the carrying gas together, spraying them into the flame for nucleation and growth, and collecting to obtain LSC-GDC composite powder materials, wherein the carrying gas is air or oxygen, and the flow rate of the carrying gas is 3-15 L / min; Wherein, the nanoparticle size of the LSC-GDC composite powder material is 1-10 nm.
2. The method for synthesizing a LSC-GDC composite powder material according to claim 1, characterized in that: The solvent comprises deionized water and ethanol, and the volume fraction x of the deionized water in the solvent satisfies 8≤x≤14%.
3. The method for synthesizing a LSC-GDC composite powder material according to claim 1, characterized in that: The molar concentration of the metal element in the precursor solution is 0.01-1 mol / L, and the metal element is La, Sr, Co, Ce and Gd.
4. The method for synthesizing a LSC-GDC composite powder material according to claim 1, characterized in that: The pumping rate of the precursor solution is 0.1-10 mL / min.
5. The method for synthesizing a LSC-GDC composite powder material according to claim 1, characterized in that: The tolerance factor t of the nanoparticles of the LSC-GDC composite powder material satisfies t∈[0.7,1.1], and t is calculated according to formula (1): Among them, r A is the ionic radius of La ion, r B is the ionic radius of the Sr ion, r O is the ionic radius of O ion.
6. The method for synthesizing a LSC-GDC composite powder material according to claim 1, characterized in that: The flame is generated by igniting a mixture of combustible gas and oxidant, the combustible gas is gaseous hydrocarbon fuel, the oxidant is air or oxygen, the flow rate of the combustible gas is 0.5-6L / min, and the flow rate of the oxidant is 2.5-30L / min.
7. The method for synthesizing a LSC-GDC composite powder material according to claim 6, characterized in that: The flame type of the flame is a plane flame, and the equivalence ratio of the plane flame is 0.9-1.
1.
8. The method for synthesizing a LSC-GDC composite powder material according to claim 7, characterized in that: The plane flame is generated by igniting a mixture of methane and air, the flow rate of methane is 1.5 L / min, and the flow rate of air is 15 L / min.
9. An air electrode, characterized in that: The air electrode comprises a first multiphase powder material, and the first multiphase powder material is a LSC-GDC multiphase powder material synthesized by the synthesis method according to any one of claims 1 to 8.
10. An air electrode as claimed in claim 9, characterized in that: The air electrode is composed of a first composite powder material and a second composite powder material, wherein the second composite powder material is an LSC-GDC composite powder material prepared by spray drying, and the mass of the first composite powder material accounts for 10-50% of the total mass of the first composite powder material and the second composite powder material.
11. A solid oxide battery, characterized in that: The solid oxide battery comprises an air electrode as claimed in claim 9.
Citation Information
Patent Citations
Method for researching electrochemical performance of battery composite nano cathode LSC-GDC
CN116337965A
High-entropy oxide nano material synthesis method based on flame spray pyrolysis technology
CN118344148A
